THE ROLE OF NARCOTICS AND PSYCHOTROPHIC SUBSTANCES IN SOCIETY - Sarvar A. Khakimov; Dilshod E. Gulyamov; Malika R. Salimova (Web of Journals Publishing, 2024)
A disease condition caused by temporary or chronic consumption of narcotic and psychotropic substances, addiction, or rather, natural or synthetic toxic substances (certain medicinal substances). Narcotics and psychotropic drugs cause profound changes in the somatic and mental state of the body and lead the addict to decline. In narcotic and psychotropic patients, there is an uncontrollable desire to use drugs, the need for the amount of the drug, and mental and physical dependence increase. Narcotics and psychotropics begin slowly and continue chronically. At first, drugs cause euphoria, euphoria (see Euphoria), and make you happy, and then it gradually turns into a disease. Narcotic drugs and psychotropic drugs can escalate in 2 days. In the first case, long-term and incorrect intake of drugs prescribed by a doctor and having the property of improving the patient's spirit and mood; to increase the amount (dose) of medicine in order to get rid of pain, insomnia and other ailments; even if there is no need for the drug after recovering from the pain, as a result of continuing to take it, the narcotic effect and quantity of the drug will increase, eventually the addiction to the drug will increase, and it will become a humor. The second case is the use of drugs for conscious pleasure.
Keywords: narcotic-psychotrophic substances, society.